Birthrate, Sovereignty and Development: The Restrictive Regulations to Family Planning in the Third Peronist Government (Argentina, 1973-1976) - Karina Alejandra Felitti (Revista Estudos Feministas, 2008)
The intensive growth of the world population during the second postwar period expanded the fear of an imminent depletion of natural resources and the destabilization of the capitalist system. Meanwhile the “population bomb” became a threat in the Cold War context, in Argentina the situation was the opposite, with a persistent birth rate decline. The third Peronist government (1973-1976) included the problem of the demographic fall among its priorities and the originality of its plan of action was that, for the first time in this country, coercive regulations prevented the free access to contraception. In this article we propose to analyze these policies, the contradictions inside the government regarding the best way to proceed, its repercussions and the resistance they produced.